Influence of Age on Upper Arm Cuff Blood Pressure Measurement. Issue 3 (March 2020) - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Black, J. Andrew; Bos, Willem J.; Chen, Chen-Huan; Cheng, Hao-Min; Cremer, Antoine; Dwyer, Nathan; Fonseca, Ricardo; Hughes, Alun D.; Kim, Hack-Lyoung; et al.
Abstract : Blood pressure (BP) is a leading global risk factor. Increasing age is related to changes in cardiovascular physiology that could influence cuff BP measurement, but this has never been examined systematically and was the aim of this study. Cuff BP was compared with invasive aortic BP across decades of age (from 40 to 89 years) using individual-level data from 31 studies (1674 patients undergoing coronary angiography) and 22 different cuff BP devices (19 oscillometric, 1 automated auscultation, 2 mercury sphygmomanometry) from the Invasive Blood Pressure Consortium. Subjects were aged 64±11 years, and 32% female. Cuff systolic BP overestimated invasive aortic systolic BP in those aged 40 to 49 years, but with each older decade of age, there was a progressive shift toward increasing underestimation of aortic systolic BP ( P <0.0001). Conversely, cuff diastolic BP overestimated invasive aortic diastolic BP, and this progressively increased with increasing age ( P <0.0001). Thus, there was a progressive increase in cuff pulse pressure underestimation of invasive aortic PP with increasing decades of age ( P <0.0001). These age-related trends were observed across all categories of BP control. We conclude that cuff BP as an estimate of aortic BP was substantially influenced by increasing age, thus potentially exposing older people to greater chance for misdiagnosis of the true risk related to BP. Abstract : Supplemental Digital Content is available in the text.